Leukotriene C4 biosynthesis in isolated August rat peritoneal leukocytes - J. M. Huebner; R. R. Eversole; W. F. Jackson; C. D. Mackenzie; S. R. Stapleton; L. J. Beuving (Hindawi Limited, 1996)
The mixed leukocyte population obtained from the peritoneum of the August rat is a potentially important experimental model of inherent eosinophilia that has not been well characterized. In the present study, isolated cell preparations generated a concentration-dependent release of leukotriene (LT) C4 when exposed to the Ca2+ ionophore A23187, reaching maximal stimulation at 5.0 μM. This response was inhibited by the 5-lipoxygenase activating protein antagonist MK-886 (0.1 μM), nominally Ca2+ and Mg2+-free incubation media and by activation of protein kinase C via phorbol 12-myristate 13-acetate (50 nM). These findings establish a model system for investigating LTC4 profiles contingent with innate peritoneal eosinophilia and are consistent with the hypothesis that cellular LTC4 biosynthesis is phosphoregulated.